Preparation of low cement ultra-high performance concrete - Azmee, N.M. (Springer, 2020)
Technology advancement in concrete industry and expanding interest for high quality construction materials have prompted the development of ultra-high performance concrete (UHPC). Despite of many advantages gained using this performance-based concrete, however, conventional UHPC recipe raises many concerns especially on sustainability issues. Producing UHPC, requires relatively high amount of cement content and often the compositions are not optimized. Low cement UHPC was proposed to minimize the economic and environmental disadvantages of current UHPC by incorporating high content of supplementary cementing materials (SCM). An experimental program was carried out to evaluate the effect of SCM combinations on workability and compressive strength. It was found that good consistency and highest strength of low cement UHPC could be achieved with binary combination of fly ash and ultrafine calcium carbonate as SCM replacing up to 50 of cement. Enhancement of compressive strength as early as 7 days at 12.5 followed by 8 at 28 days and 20 at 90 days were observed in this low cement UHPC. Â© Springer Nature Singapore Pte Ltd 2020.